Improving acute stroke care in regional hospitals: clinical evaluation of the Victorian Stroke Telemedicine program. Issue 8 (7th April 2020) - Bladin, Chris F; Kim, Joosup; Bagot, Kathleen L; Vu, Michelle; Moloczij, Natasha; Denisenko, Sonia; Price, Chris; Pompeani, Nancy; Arthurson, Lauren; Hair, Casey; Rabl, Justin; O'Shea, Mick; et al.
Abstract: Objectives: To evaluate the impact of the Victorian Stroke Telemedicine (VST) program during its first 12 months on the quality of care provided to patients presenting with suspected stroke to hospitals in regional Victoria. Design: Historical controlled cohort study comparing outcomes during a 12‐month control period with those for the initial 12 months of full implementation of the VST program at each hospital. Setting: 16 hospitals in regional Victoria that participated in the VST program between 1 January 2010 and 30 January 2016. Participants: Adult patients with suspected stroke presenting to the emergency departments of the participating hospitals. Main outcome measures: Indicators for key processes of care, including symptom onset‐to‐arrival, door‐to‐first medical review, and door‐to‐CT times; provision and timeliness of provision of thrombolysis to patients with ischaemic stroke. Results: 2887 patients with suspected stroke presented to participating emergency departments during the control period, 3178 during the intervention period; the patient characteristics were similar for both periods. A slightly larger proportion of patients with ischaemic stroke who arrived within 4.5 hours of symptom onset received thrombolysis during the intervention than during the control period (37% v 30%). Door‐to‐CT scan time (median, 25 min [IQR, 13–49 min] v 34 min [IQR, 18–76 min]) and door‐to‐needle time for stroke thrombolysis (73 min [IQR, 56–96 min] v 102 min [IQR, 77–128 min]) were shorter during the intervention. The proportions of patients who received thrombolysis and had a symptomatic intracerebral haemorrhage (4% v 16%) or died in hospital (6% v 20%) were smaller during the intervention period. Conclusions: Telemedicine has provided Victorian regional hospitals access to expert care for emergency department patients with suspected acute stroke. Eligible patients with ischaemic stroke are now receiving stroke thrombolysis more quickly and safely.